Le amnistie di Dikaia e il giuramento nella riconciliazione post-stasis (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
Amnesty in the Greek world has always been unilaterally identified with the wellknown Athenian provision of 403/2 BCE. The article aims at providing an analysis of the inscription SEG 57, 576 coming from Dikaia in Chalkidike which, despite containing elements of great interest, has so far received scarce attention from scholars after its publication in 2007. The inscription contains a reconciliation agreement drafted probably in 362/1 after a stasis and it consists of six decrees and a civic oath. The Macedonian king Perdikkas III forbids the prosecution of those responsible for any crime committed during civil war through the prescription μὴ μνησικακεῖν. Alongside this measure, the polis also concedes the possibility to judge homicide cases initiated before the outbreak of the stasis; the unjudged actions would be declared ἀπόκλε(ι)τα, meaning they would be annulled (third decree). One of the most relevant aspects is the fact that, like the other decrees, the civic oath has a binding value and does not merely represent an appendix to the decrees, but rather the starting point for the interpretation of the other provisions. A further element is the fact that the amnesty reported in the third decree does not coincide with that expressed by the formula μὴ μνησικακεῖν contained in the oath and it pertains to a period preceding that of the stasis.
Keywords: amnesty; Dikaia; reconciliation; oath; stasis